Tren Publikasi pada Konstruk Masyarakat Belajar - Imam Gunawan (Proceedings Series of Educational Studies, 2023)
Abstract: The learning community is a paradigm in education that affirms that learning outcomes are obtained from positive cooperation with other individuals. In the context of a learning community, it is necessary to develop a good curriculum to the level of classroom management in order to promote students lifelong learning. The purpose of this study was to find out significant documents from the construct of the learning community. The data source was obtained from the Google Scholar database with a total of 1000 documents in the period 2003-2022. Publish or Perish software is used to extract data. The results confirmed an increase in the number of publications of each developmental period (Birth, Development, Adulthood). The study presents 15 significant documents based on the number of citations in each developmental period and analysis of the content of the documents. Implications of the findings are discussed and future research opportunities are suggested.Keywords: Community Learning, Content Analysis, Publish or PerishAbstrak: Masyarakat belajar merupakan sebuah paradigma dalam pendidikan yang menegaskan bahwa hasil belajar diperoleh dari adanya kerjasama yang positif dengan individu lain. Dalam konteks masyarakat belajar, diperlukan pengembangan kurikulum yang baik sampai pada tataran pengelolaan kelas agar dapat mempromosikan siswa belajar sepanjang hayat. Tujuan penelitian ini adalah untuk mengetahui dokumen signifikan dari konstruk masyarakat belajar. Sumber data diperoleh dari database Google Scholar dengan total 1000 dokumen pada rentang waktu 2003-2022. Perangkat lunak Publish or Perish digunakan untuk mengekstrak data. Hasilnya menegaskan adanya peningkatan jumlah publikasi dari setiap periode perkembangan (Kelahiran, Perkembangan, Dewasa). Studi ini menyajikan 15 dokumen signifikan berdasarkan jumlah sitasi pada setiap periode perkembangan dan analisis isi dari dokumen. Implikasi dari temuan didiskusikan dan peluang penelitian masa depan disarankan.Kata kunci: masyarakat belajar, analisis isi, publish or perish